Proses Berpikir Kreatif Siswa Tipe Linguistik dalamPemecahan Masalah Biologi - Imelda Aisah Sarip; Kamid Kamid; Bambang Hariyadi (Universitas Jambi, 2013)
The aim of this research is to describe creative thinking process of linguistic type student in biology problem solving. This research is conducted to linguistic intelligence type of subject at SMPN 6 Kota Jambi. SL the subject was selected based on the aim of the research. Data collection is conducted by interview and a modified think aloud method. Data is analyzed based on creative thinking process purposed by Polya.The result of this research shows that SL could find and arrange the given problems and collect data correctly and appropriately. The problem solving steps is done systematically to the end of problem solving process. The last steps problem solving, SL does checking while doing scratching to make sure that the written answers meet her need.